Human Relations and Education: The Perspective of Omar Mohammad al-Toumy al-Syaibany: Contribution to the Development of Humanistic-Based Education - Khairul Fata; Muzammil (CV Edujavare Publishing, 2026)
This study addresses the dominance of cognitive-instrumental approaches in modern education, which often neglect students' moral, spiritual, and social development. While Western humanistic education seeks to restore human values, it remains limited in integrating spirituality from an Islamic perspective. This study aims to examine Asy-Syaibani's concept of the multidimensional human being, analyze the educator–student relationship within his educational philosophy, and explain the contribution of spiritual-moral integration to an Islamic humanistic education model. Using a qualitative library research approach, the study analyzes Falsafatu at-Tarbiyah al-Islamiyyah by Omar Muhammad at-Toumy Asy-Syaibani as the primary source, supported by relevant scholarly literature. The data were analyzed using the Miles and Huberman interactive model. The findings indicate that Asy-Syaibani conceptualizes humans as integrated physical, intellectual, spiritual, and social beings, providing the philosophical basis for holistic education. His dialogical, student-centered, and exemplary educational relationship reflects core humanistic principles while grounding them in Islamic ethics. Furthermore, the integration of spiritual-moral values ​​throughout objectives, curriculum, and learning processes offers a distinctive Islamic humanistic model that complements secular humanism through theocentric orientation and the pursuit of human beings.